Health System through the Eyes of a Doctor from Rural Nepal - Hamal, P K; shrimal, S R; Khadka, M; Sapkota, B; Thapa, J; Pariyar, J; Magar, A (Journal of Nepal Health Research Council, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE NE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Its almost 30 years of declaration of Alma-Ata for primary healthcare policy the health system in Nepal still facing shortage of trained medical doctors and health professionals reaching remote and rural part of the country to provide quality health services. There are number of issues such as financial or non-financial incentives, professional advancements, educational opportunities and workplace environment. Healthcare delivery system in Nepal is failing to meet the healthcare need of the general public and needs discussion and revision. However, despite of so many challenges more doctors are willing to work in the remote and rural Nepal. The government has to come out with effective planning and policy regarding health system and human resource for health. In this context, an attempt has been made for a analytical perspective from a medical doctor point of view to highlight some of the pertinent local and policy related issues to improve Health System in Nepal. Keywords: doctor, health, health system, Nepal, policy